Globalization and the distribution of wealth : the Latin American experience, 1982-2008 - Kacowicz, Arie Marcelo (Cambridge University Press, 2013)
"The effect of globalization on poverty and inequality is a key issue in contemporary international politics yet it has been neglected in international relations and comparative politics literatures. Arie M. Kacowicz explores the complex relationship between globalization and the distribution of wealth as a political problem in international relations, analyzing them through the prism of poverty and inequality. He develops a political framework (an 'intermestic model') which captures the interaction between the international and the domestic domains and explains those effects with a particular emphasis upon the state and its relations with society. He also specifies the different hypotheses about the possible links between globalization and the distribution of wealth and tests them in the context of Latin America during the years 1982-2008, with a particular focus on Argentina and the deep crisis it experienced in 2001-2"--